Interação fósforo-silício-flúor em materiais de solo oxídico e uso benéfico de subproduto da indústria de fertilizantes fosfatados na soja - Borges, Camila Silva (2018)
Phosphorus (P) and calcium (Ca) are macronutrients of plants and contribute to important metabolic functions. However, silicon (Si), although not considered as such, is classified as a beneficial element in recognition of its environmental conditioning effect. Different from the others fluorine (F), it is essential only for humans, but its presence in the soil up to certain concentrations may contribute to the neutralization of aluminum and desorption of previously adsorbed phosphorus. In the phosphoric acid manufacturing process, the fertilizer industry emits large quantities of gases containing Si and F, which must be captured and neutralized to avoid atmospheric pollution. The gas capture and neutralization reaction makes it possible to obtain a by-product containing Ca, Si and F that has potential for reutilization with a focus on agricultural use. The objective of this study is to evaluate the potential use of this byproduct as soil conditioner. For this, adsorption, desorption and displacement experiments involving Si, P and F were carried out in horizons of a Plintossolic Yellow Latosol, as well as the evaluation of two soybean crops in the same soil after application of the by-product containing Si , Ca and F. The soil characterization was performed through fertility, load balance, texture, specific surface area, porosity, sulfuric attack, crystallinity of iron and aluminum sesquioxides and X-ray diffraction and by-product by chemical composition and relative neutralization power. The sorptive capacity of P, Si and F was performed in NaCl solution 30 mmol L-1, with the pH adjusted to 5.5, using the following concentrations of each of the elements: 0; 0.05; 0.10; 0.20; 0.40; 0.80 and 1.6 mmol L-1. Desorption was performed by the addition of 30 mmol L-1 NaCl at pH 5.5 without addition of the respective elements. In the displacement, the samples were previously adsorbed with increasing doses of P (0, 0.003, 0.008, 0.016, 0.032, 0.113, 0.226, 0.807, 2.266 and 4.520 mmol L-1) and in the desorption solution 0.6 mmol L-1 of Si and F mono and multielement were added to promote the displacement of P previously adsorbed. The Langmuir and Freundlich models were used to obtain the soil sorption parameters and the desorption adjusted to the regression curves. For the agronomic evaluation, two soybean cultivations were carried out in an area with different types of management using the by-product at 500 and 1000 kg ha-1 and a commercial source of Si at 400 and 800 kg ha- 1. The experimental design was in blocks, containing a control treatment and the respective doses of each of the products considering the same contribution of Si. The variables responses consisted of evaluations carried out in the soil and in the culture. The Langmuir and Freundlich models were adequate to explain the sorption behavior of the elements and allowed to obtain the parameters that indicated higher adsorption capacity of F, followed by P and Si for the surface horizon (Ap) and P, F and Si for the subsurface horizons (Bw and Bf). It was not observed the P displacement by Si and F, being the organic matter and the iron and aluminum oxide content the parameters that most influenced the adsorption and desorption of these elements in the soil. The parameters evaluated in the soil and in the crop did not make it possible to prove the effect of the byproduct in the two soybean crops. However, the possible residual effect of the by-product in subsequent years should be assessed.